Extract of mangosteen increases high density lipoprotein levels in rats fed high lipid - Dwi Laksono Adiputro; M. Aris Widodo; Rochmad Romdoni; Djanggan Sargowo (Universa Medicina, 2013)
BACKGROUND In cardiovascular medicine, Garcinia mangostana has been used as an antioxidant to inhibit oxidation of low density lipoproteins and as an antiobesity agent. The effect of Garcinia mangostana on hyperlipidemia is unknown. The aim of this study was to evaluate the effect of an ethanolic extract of Garcinia mangostana pericarp on lipid profile in rats fed a high lipid diet. METHODS A total of 40 rats were divided into five groups control, high lipid diet, and high lipid diet + ethanolic extract of Garcinia mangostana pericarp at dosages of 200, 400, and 800 mg/kg body weight. The control group received a standard diet for 60 days. The high lipid diet group received standard diet plus egg yolk, goat fat, cholic acid, and pig fat for 60 days with or without ethanolic extract of Garcinia mangostana pericarp by the oral route. After 60 days, rats were anesthesized with ether for collection of blood by cardiac puncture. Analysis of blood lipid profile comprised colorimetric determination of cholesterol, triglyceride, low density lipoprotein (LDL), and high density lipoprotein (HDL). RESULTS From the results of one-way ANOVA it was concluded that there were significant between-group differences in cholesterol, trygliceride, LDL, and HDL levels (p=0.000). Ethanolic extract of Garcinia mangostana pericarp significantly decreased cholesterol, trygliceride, and LDL levels, starting at 400 mg/kg body weight (p=0.000). Ethanolic extract of Garcinia mangostana pericarp significantly increased HDL level starting at 200 mg/kg body weight (p=0.000). CONCLUSION Ethanolic extract of Garcinia mangostana pericarp has a beneficial effect on lipid profile in rats on a high lipid diet.